Project-Based Learning E-Modules Based on Research Results on the Nutritional Content of Sawi Asin (Fermented Mustard) - Febriyanti, Nisa; Rahayu, Hanum Mukti; Setiadi, Anandita Eka (Jurnal Inovasi Pendidikan IPA, 2023)
The project-based learning model focuses on directing students to be more active in learning. The learning model will be effective if combined with e-module media. Because e-modules provide facilities for students to learn independently. One of the materials in class XII Biology that is applied in e-modules is biotechnology related to local potential, namely Sawi Asin fermentation. The study aims to develop project-based learning e-modules based on research results on the nutritional content of Sawi Asin fermentation. The research method uses Research and Development which adapts the Alessi and Trolip development model. There are three stages carried out, namely, planning (planning), designing (design), and developing (development). The results of e-module validation by media experts showed an average score of 94.22% (very feasible), material experts 80.83% (feasible), and language experts 87.333% (very feasible). The results of the small group test with 12 students of class XII IPA showed an average value of 81.09% (very positive) and the large group test with 32 students of class XII was IPA 87.04% (very positive). It can be concluded that the project-based learning e-module based on the results of research on the nutritional content of Sawi Asin fermentation developed is very feasible to use and gets a very positive response from students.Keywords: E-module, Development, Project Based Learning